Relações interpessoais e poder e seus impactos na cultura organizacional: um estudo de caso no curso de graduação em Engenharia Ambiental da Universidade Federal do Espírito Santo - Campos, Lucas Pereira (2013)
From studies started in the early decades of the twentieth century, it appears that productivity and culture organizations are directly impacted by interpersonal relationships developed among the members of the institutions. In public organizations present, unique features to this type of administration result in some peculiarities in the way such relationships occur. In the case of an undergraduate course of a Federal University in Brazil, the existence of three groups of people very well defined, which often manifest divergent objectives, and other unique characteristics of a public institution of higher education, resulting in complex interpersonal relationships, bringing direct implications for organizational culture.